1998
DOI: 10.1093/emboj/17.22.6437
|View full text |Cite
|
Sign up to set email alerts
|

Structural origins of gentamicin antibiotic action

Abstract: Aminoglycoside antibiotics that bind to the ribosomal A site cause misreading of the genetic code and inhibit translocation. The clinically important aminoglycoside, gentamicin C, is a mixture of three components. Binding of each gentamicin component to the ribosome and to a model RNA oligonucleotide was studied biochemically and the structure of the RNA complexed to gentamicin C1a was solved using magnetic resonance nuclear spectroscopy. Gentamicin C1a binds in the major groove of the RNA. Rings I and II of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
255
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(273 citation statements)
references
References 30 publications
(52 reference statements)
7
255
0
1
Order By: Relevance
“…and Streptomyces spp. protect their 30S ribosome through methylation of its 16S rRNA at the aminoglycoside-binding A site (10,30). For example, Kgm, which was isolated from Micromonospora purpurea (28), methylates G1405, and Kam, which was isolated from Streptomyces tenjimariensis (24), methylates A1408 (2).…”
Section: Discussionmentioning
confidence: 99%
“…and Streptomyces spp. protect their 30S ribosome through methylation of its 16S rRNA at the aminoglycoside-binding A site (10,30). For example, Kgm, which was isolated from Micromonospora purpurea (28), methylates G1405, and Kam, which was isolated from Streptomyces tenjimariensis (24), methylates A1408 (2).…”
Section: Discussionmentioning
confidence: 99%
“…Because the aminoglycoside antibiotic gentamicin binds to the 16S ribosomal RNA on the 30S small ribosomal subunit A site of the assembled ribosome (32), it provides a convenient alternative marker of active translation. After exposure of G. obscuriglobus cells to GTTR, we observed Texas Red signal only in regions distant from the nucleoid(s) (Fig.…”
Section: Use Of Immunoelectron Microscopy and An Antibody-independentmentioning
confidence: 99%
“…21,22 Recent structural and biochemical studies have suggested a potential mechanism by which aminoglycosides achieve their antitranslational effects. 23,12,[24][25][26][27][28]13,29,14,19,30,15 According to this mechanism, A1492 and A1493 are in conformational equilibria between intrahelical and extrahelical states. When in their extrahelical states, both bases engage in interactions with minihelix formed by the mRNA codon and the tRNA anticodon.…”
Section: Greater Extents Of Aminoglycoside-induced Reduction In the Mmentioning
confidence: 99%